The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jmri.25888
|View full text |Cite
|
Sign up to set email alerts
|

Can MR enterography screen for perianal disease in pediatric inflammatory bowel disease?

Abstract: 3 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1638-1645.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…To minimize the time-consuming scanning processes and patient inconvenience, several centers in Korea, including ours, are currently performing pelvic MRI as an adjunct to regular MRE in clinical practice. Studies have shown that this approach is feasible and sensitive in detecting major perianal lesions [ 21 24 ]. A study on children with perianal CD has recently reported that MRE is capable of detecting perianal diseases with high specificity and moderate sensitivity in pediatric inflammatory bowel disease patients when using a standard technique [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To minimize the time-consuming scanning processes and patient inconvenience, several centers in Korea, including ours, are currently performing pelvic MRI as an adjunct to regular MRE in clinical practice. Studies have shown that this approach is feasible and sensitive in detecting major perianal lesions [ 21 24 ]. A study on children with perianal CD has recently reported that MRE is capable of detecting perianal diseases with high specificity and moderate sensitivity in pediatric inflammatory bowel disease patients when using a standard technique [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that this approach is feasible and sensitive in detecting major perianal lesions [ 21 24 ]. A study on children with perianal CD has recently reported that MRE is capable of detecting perianal diseases with high specificity and moderate sensitivity in pediatric inflammatory bowel disease patients when using a standard technique [ 24 ]. Considering its feasibility and accuracy, along with the high incidence of perianal fistulizing disease in children and adolescents in Korea, a pelvic MRI adjunct to MRE could be considered as a routine examination at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 AlSabban et al noted a high sensitivity with MR enterography in detection of perianal disease in pediatric patients. 17 Pelvic MR imaging is currently the standard for imaging perianal CD. 4 More recently, Cattapan et al found that although contrastenhanced MR studies could improve radiologist's confidence, non-contrast MR studies had similar diagnostic efficacy in identifying perianal fistulas and their complications.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an adult metaanalysis of four studies showed MRI sensitivity and specificity for fistula detection were 87% and 69%, respectively, with greater specificity than US at 43% [57]. With standard pediatric MRE, which included this region, the sensitivity and specificity were 82% and 100% for perianal disease [58]. Unlike MRE, however, for MRI pelvis in this variant, oral contrast material is not necessary.…”
Section: Variant 3: Child Known Crohn Disease Disease Surveillance Or...mentioning
confidence: 99%